2022
DOI: 10.1111/jdv.18179
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and familial clustering of infantile haemangiomas: a multicentre study

Abstract: Background The exact incidence of infantile haemangiomas (IH) in the Chinese population is still unknown. A positive family history of IH was considered as a risk factor for the development of IH.Objectives This study aims to investigate the incidence of IH in the Chinese population and the mechanism of family history increases the risk for IH development.Methods A total of 2489 women and their newborns were enrolled in the prospective study. All newborns were followed up for 12 months to determine whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Figure 1 lists the screening process and reasons for exclusion. 27 studies 7–9,27–50 investigated prevalence, mainly in America, Germany, Canada, Israel, Japan, Australia, Netherlands, Denmark, China, Mali, and Brazil. 27 studies 7,12,28,35–37,44,45,47,50–67 reported the distribution of IH lesions, and 14 studies 7,12,35,50–52,55,57,59,61,63,64,68,69 surveyed the occurrence of complications.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 1 lists the screening process and reasons for exclusion. 27 studies 7–9,27–50 investigated prevalence, mainly in America, Germany, Canada, Israel, Japan, Australia, Netherlands, Denmark, China, Mali, and Brazil. 27 studies 7,12,28,35–37,44,45,47,50–67 reported the distribution of IH lesions, and 14 studies 7,12,35,50–52,55,57,59,61,63,64,68,69 surveyed the occurrence of complications.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we observed vaginal bleeding, preeclampsia, placental abnormalities, placenta previa, premature rupture of membranes, anemia, previous miscarriage, periconceptional use of drugs, maternal b-blocker, in vitro fertilization, amniocentesis, chorionic villus sampling dependent associations for the occurrence of IH. 7,16,31,40,44,46,55,63,70,72 In addition, Smith 8…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, IHs often occur in sporadic cases from various regions and racial/ethnic groups, although a few familial aggregations that are considered to be genetically related may exist ( 5 ). Recently, a multicenter study found an increased risk of IHs in siblings of patients with IHs, which is considered to be due to the familial clustering of prenatal risk factors ( 6 ).…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%